EXTENDED-SPECTRUM BETA-LACTAMASE PRODUCING GRAM NEGATIVE BACTERIA IN IRAN - Leylabadlo, Hamed Ebrahimzadeh; Pourlak, Tala; bialvaei, Abed Zahedi; Aghazadeh, Mohammad; Asgharzadeh, Mohammad; Kafil, Hossein Samadi (African Journal of Infectious Diseases (AJID), 2017)
Background: The emergence and spread of extended spectrum β-lactamase (ESBL)-producing Gram- negative bacteria(GNB), particularly in Enterobacteriaceae, Acinetobacter baumannii, and Pseudomonas aeruginosa, have increased all overthe world. ESBLs are characterized by their ability to hydrolyze β-lactams, early cephalosporins, oxyimino-thiazolylcephalosporins, and monobactams, but not cephamycins or carbapenems. The rate of nosocomial infections caused byESBL-producing GNB in Asia Pacific has increased and several studies have identified their prevalence in the region. Theaim of this study is to review the prevalence of ESBL-producing GNB in the West Asia and the Middle East with aparticular focus on Iran.Materials and Methods: The available evidence from various studies (Microbia and clinical studies, retrieved from thePubMed, and Scopus databases) regarding the ESBL producing Gram negative bacteria in Iran were evaluated.Results: In almost all parts of the country, high resistance has been observed, especially in the central part of Iran. Up to89.8% Escherichia coli, 72.1% Klebsiella pneumonia, 84.2% Acinetobacter baumannii, and 83.8% Pseudomonasaeruginosa isolates are ESBL positive.Conclusion: The present study showed the increasing prevalence of ESBLs in different regions of Iran, which could beuseful to strategic policy towards reducing reduce their prevalence.